The major subunit of widespread competence pili exhibits a novel and conserved type IV pilin fold - Sheppard, Devon (J Biol Chem, 2020)
Type IV filaments (T4F), which are helical assemblies of type IV pilins, constitute a superfamily of filamentous nanomachines virtually ubiquitous in prokaryotes that mediate a wide variety of functions. The competence (Com) pilus is a widespread T4F, mediating DNA uptake (the first step in natural transformation) in bacteria with one membrane (monoderms), an important mechanism of horizontal gene transfer. Here, we report the results of genomic, phylogenetic, and structural analyses of ComGC, the major pilin subunit of Com pili. By performing a global comparative analysis, we show that Com pili genes are virtually ubiquitous in Bacilli, a major monoderm class of Firmicutes. This also revealed that ComGC displays extensive sequence conservation, defining a monophyletic group among type IV pilins. We further report ComGC solution structures from two naturally competent human pathogens, Streptococcus sanguinis (ComGC(SS)) and Streptococcus pneumoniae (ComGC(SP)), revealing that this pilin displays extensive structural conservation. Strikingly, ComGC(SS) and ComGC(SP) exhibit a novel type IV pilin fold that is purely helical. Results from homology modeling analyses suggest that the unusual structure of ComGC is compatible with helical filament assembly. Because ComGC displays such a widespread distribution, these results have implications for hundreds of monoderm species.